2006
DOI: 10.1152/japplphysiol.00187.2005
|View full text |Cite
|
Sign up to set email alerts
|

Rehydration with glycerol: endocrine, cardiovascular, and thermoregulatory responses during exercise in the heat

Abstract: The impact of rehydration with glycerol on cardiovascular and thermoregulatory responses during exercise in the heat was studied in eight highly trained male cyclists. Each subject completed three dehydration-rehydration experimental trials that differed only in the rehydration treatment, each separated by 7 days. Before each experimental day, subjects dehydrated to -4% of their body weight by exercise and water restriction. The experimental treatments were as follows: no fluid (NF), glycerol bolus (1 g/kg bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 49 publications
3
43
1
Order By: Relevance
“…In addition to its osmotic and moisturizing effect, increasing circulating levels of glycerol stimulate hepatic gluconeogenesis, increasing the number of substrates available for energy supply (Kavouras et al, 2006). Under HS, EI was increased with increasing GLYC levels (p<0.05), because the supplementation with 2% GLYC contributed with 53 kcal, in addition of the energy consumed in the feed.…”
Section: Effects Of the Addition Of Pure Glycerin Supplementation In mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to its osmotic and moisturizing effect, increasing circulating levels of glycerol stimulate hepatic gluconeogenesis, increasing the number of substrates available for energy supply (Kavouras et al, 2006). Under HS, EI was increased with increasing GLYC levels (p<0.05), because the supplementation with 2% GLYC contributed with 53 kcal, in addition of the energy consumed in the feed.…”
Section: Effects Of the Addition Of Pure Glycerin Supplementation In mentioning
confidence: 99%
“…Studies on glycerol consumption via drinking water for animals and human athletes have shown that this substance has hyper-moisturizing properties due to the osmotic effect of glycerol in the body, supporting body fluid regulation when physical activities are performed in high environmental temperatures (Schott et al, 2001;Coutts et al, 2002;Kavouras et al, 2006;Patlar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case studies were excluded from the analysis (29,30). Studies comparing the ability of water and water + glycerol to replace exercise-induced fluid losses after exercise were not considered for the analysis on the basis that the hydration dynamic in such conditions might not be representative of what occurs when fluids are administered in a euhydrated state, and those studies were not intended nor designed to look at the effect of hyperhydration (44,86).…”
Section: Magnitude Of the Effect Of Gih On Fluid Retentionmentioning
confidence: 99%
“…Case studies were excluded from the analysis (29). For reasons previously explained, studies that examined EP after rehydration with water and water + glycerol in hypohydrated athletes were not included in the analysis (44,86). Moreover, in an effort to not mix findings, we did not include in the analysis results of a study comparing the effect of GIH and WIH on EP while subjects were wearing chemical protective clothing (49).…”
Section: Magnitude Of the Effects Of Gih On Epmentioning
confidence: 99%